Hybrid Polymer Composites Used in the Arms Industry: A Review - Czech, Kamil (Materials (Basel), 2021)
Polymer fiber composites are increasingly being used in many industries, including the defense industry. However, for protective applications, in addition to high specific strength and stiffness, polymer composites are also required to have a high energy absorption capacity. To improve the performance of fiber-reinforced composites, many researchers have modified them using multiple methods, such as the introduction of nanofillers into the polymer matrix, the modification of fibers with nanofillers, the impregnation of fabrics using a shear thickening fluid (STF) or a shear thickening gel (STG), or a combination of these techniques. In addition, the physical structures of composites have been modified through reinforcement hybridization; the appropriate design of roving, weave, and cross-orientation of fabric layers; and the development of 3D structures. This review focuses on the effects of modifying composites on their impact energy absorption capacity and other mechanical properties. It highlights the technologies used and their effectiveness for the three main fiber types: glass, carbon, and aramid. In addition, basic design considerations related to fabric selection and orientation are indicated. Evaluation of the literature data showed that the highest energy absorption capacities are obtained by using an STF or STG and an appropriate fiber reinforcement structure, while modifications using nanomaterials allow other strength parameters to be improved, such as flexural strength, tensile strength, or shear strength.